UPAYA JEPANG DIBAWAH PEMERINTAHAN SHINZO ABE DALAM MENINGKATKAN PERTAHANAN MILITER - Ayu, Ananda F (Transformasi, 2015)
This study describes how Japan's efforts to improve its military . The Japanese effort whichwill issue a policy in which Japan can actively participate in military activities. Japan hasexperienced many developments after the Cold War to become one of the most advancedmilitary in East Asia . This is due to the encouragement of the US desire to keep the area fromEast Asia to North Korean military forces . National Defense Program Guidelines, 2010brings a new change in the concept of the Japanese defense . The change lies in the existenceof the concept of Dynamic Defense Force to replace the Basic Defense Force that has beenused since the National Defense Program Outline in 1976. That is because Abe has a positionand legitimacy are more powerful than ever , with the support of the LDP as a party majoritycontrol of parliament , and the level of acceptance of people who remain good. Defensepolicies that have been issued by Abe in the background backs regional conditions in EastAsia increasingly unsafe . Mainly related to the growing concerns of the Japanese people ofboth countries. The conclusion that can be drawn is that with these efforts can enhance Japan's defense -related millitary regional conditions in East Asia . It is also due to the support ofthe Japanese people towards security issues , including constitutional changes , will continueto grow in the futureKey Words : Security, Dynamic Defense Force, Shinzo Abe, East Asia Conflict